The Effect of Em-1® (Lactobacillus Spp.) On Growth Performance of Quails, Coturnix Japonica - Norshida, Ismail; Ahmad Syazni, Kamarudin; Mohamad Arshad, Nur-Azri; Nong Raynu, Su Wan (2018)
This study aims to determine the effectiveness of using effective microorganism as a supplement in diet on growth performance and hepatosomatic index of quails. A 14 days age quails were used in a trial in triplicate. The experiment were carried out by comparing the control (c) group with three group of effective microbe enrichment feeding in which ration was 1L EM: 250 L H2O (treatment 1), 1L EM: 550 L H2O (treatment 2) and 1L EM: 750 L H2O (treatment 3), respectively. Effective microorganism was supplemented via drinking water. Weight measurements of the quails were carried out every 7 days and growth performance parameters of the quails such as Body Weight Gain (BWG), Feed Intake (FI), Feed Conversion Ratio (FCR), Average Daily Gain (ADG) and Hepatosomatic Index (HSI) were also recorded. The data collected was analyzed for ANOVA one-way test using Statistical Package for Social Science (SPSS) software. The result shows there was significant different (p<0.05) between control group and three other treatment during week four in terms BWG, FCR, ADG and FI. The result of hepatosomatic index shows no significant different (p>0.05) between treatments. This may indicates that the effective microbe supplementation did not affect the liver metabolism.